Proposed sewerage system for Seremban town (Phase one) / Kamsiah Abd Karim - Abd Karim, Kamsiah; Taib, Halimah (1988)
A central sewerage treatment is proposed and is located at Kg Kuala Sawah. It comprises of anacrobic, facultative and maturation ponds. The effluent quality discharge by the maturation pond is expected to have BOD less than 50 mg/l with 1494 FC/100 ml.